The effect of titanium surface treatment by application of constant potential or current on the viability of pre-osteoblast cells: an in-vitro study - Cai, Wenji; Wang, Min; Hadad, Amir Ei; Zhang, Yuli; Tran, Simon D.; Shurbaji, Samar; Nasrallah, Gheyath K.; Sanz, Mariano; Omanovic, Sasha; Tamimi, Faleh (Frontiers in Bioengineering and Biotechnology, 2024)
The aim of this study was to investigate the impact of electrochemical treatments designed to decontaminate titanium on the viability of tissue cells attached to pure titanium substrates and determine safety limits for this type of treatment.Methods: Pre-osteoblast cells (pOB) were cultured and seeded onto titanium discs. The cellseeded discs were then exposed to a range of fixed direct electrical potentials (-6V to 6V) or fixed direct electrical currents (-12.5mA, -25mA, or -50mA) using a three-electrode system connected to a potentiostat. Cell viability was assessed using live/dead assay and fluorescence microscopy.Results: Exposure of cells to strong negative potentials caused cell detachment, while exposure to positive ones led to cell death on the cpTi surfaces. However, cellular viability was preserved when the electrical potentials were kept between -3 to +3 V. Cells retained 80% viability when subjected to -12.5 mA currents with an initial pOB cell count of 5x10 4 . However, when the initial cell count was elevated to 1x10 5 , the cells demonstrated the ability to withstand an even greater current (-25mA) while preserving their vitality at the same level.Conclusion: Electrical potentials can harm cells surrounding dental implants. However, this damage can be minimized by keeping the potential within a safety limit.